The Nexus of Crowdfunding and Venture Creation: A Systematic Review - Vergara, Kimberly Christie S.; Santos, Joseph Emil; Vergara, Raymond Allan (Future Science / FSH-PH Publications, 2025)
This systematic review explores how crowdfunding impacts en-trepreneurial processes, business sustainability, and venture growth. By analyzing 19 SCOPUS-indexed studies, this review iden-tifies crowdfunding’s financial and non-financial benefits, includ-ing enhanced consumer insight, market exposure, and co-creation opportunities. Crowdfunding redefines stakeholder roles, foster-ing participatory ecosystems that enable innovation, strategic scaling, and resilience. Key findings emphasize the importance of stakeholder engagement and market validation while highlighting gaps in understanding long-term sustainability, cultural influences, and evolving backer-venture dynamics. These insights provide actionable strategies for entrepreneurs and researchers to harness crowdfunding’s potential in venture creation.